Understanding pre-, peri- and post-menopausal women's intentions to perform muscle-strengthening activities using the Theory of Planned Behaviour. (March 2018) - Doherty, Julie; Giles, Melanie; Gallagher, Alison M.; Simpson, Ellen Elizabeth Anne
Highlights: This study showed low levels of muscle-strengthening activities among pre-, peri- and post-menopausal women. Knowledge and negative attitudes were important issues that influenced women's intention to perform muscle-strengthening activities. Self-efficacy and affective attitudes were identified as significant predictors of intention to perform muscle-strengthening activities. Findings were independent of menopausal status. Abstract: Although physical activity guidelines recommend muscle-strengthening activities (MSA), public health initiatives tend to focus on increasing aerobic activity and fail to mention MSA. This study sought to identify the issues influencing pre-, peri- and post-menopausal women's intentions to perform MSA with a view to informing future interventions for these populations. Mixed methods guided by the Theory of Planned Behaviour (TPB) were used to explore factors that influence women's intentions to perform MSA. In stage one, 34 women participated in either a focus group or interview. Discussions were transcribed verbatim and analysed based on menopausal status using a deductive approach. In stage two, 186 women ( M  = 47 years, SD = 9) completed a questionnaire to assess participant demographics, levels of MSA, affective and instrumental attitudes, injunctive and descriptive norms, self-efficacy and perceived behavioural control. Quantitative data were analysed using descriptive statistics, bivariate correlations, regression analyses and analysis of variances. Behavioural beliefs were: improved muscular health; psychological benefits; improved body shape. Normative beliefs were: health professionals; family members; work colleagues. Control beliefs were: equipment; motivation; time constraints; knowledge; physical capability; fear of judgement. However, these beliefs were not well established. Self-efficacy was the strongest predictor of intentions (spc 2  = 0.11) followed by affective attitudes (spc 2  = 0.09), with no significant differences on TPB variables between groups. If rising rates of musculoskeletal conditions in women are to be prevented, there is an urgent need to increase women's knowledge of recommended levels of muscle strengthening, with a view to promoting positive attitudes and enhancing women's sense of self-efficacy across all menopausal phases.